Fiber Optic Ring Resonator Sensor Detection Technique Based on Spectral Intensity Integration - Priambodo, Purnomo Sidi; Rahardjo, Sasono; Witjaksono, Gunawan; Hartanto, Djoko (Makara Journal of Technology, 2015)
Resonant field phenomenon in optical ring resonator has been a major theme for various studies and can be used for various sensor applications. The spectral response shape changes are subjects to be discussed and analyzed for detection in optical sensor system. The spectral response changes are caused by various factors ranging from refractive index of the surrounding medium, medium loss due to absorption and scattering, and coupling variation between waveguides. These optical phenomena are mostly used for bio-sensor applications, since it is free from electromagnetic interference (EMI) and non-physically destructive. In this paper, we discuss our current research in developing optical bio-sensor in the form of a fiber optic ring resonator with monochromatic laser source based on spectral integration detection method, which is sufficiently sensitive and accurate.